The effects of anxiety sensitivity on pain tolerance following exposure and avoidance : an experimental analysis : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University - Coldham-Fussell, Kim Alexandra (Massey University, 1999)
Avoidance behaviour is a prominent and pervasive component of chronic pain behaviour, and is thought to play an active part in the development and maintenance of chronic pain problems. It has been suggested that avoidance behaviour results in increased expectations and fear of pain, which in turn leads to increased avoidance (Lethem, 1983; H. Philips, 1987). However, this concept has not been examined directly to date. Fear of pain is thought to be a powerful contributor to these avoidance behaviours, in the same way that fear contributes to the avoidance behaviour associated with phobias. The efficacy of exposure therapy in the treatment of phobic avoidance has led to recent suggestions regarding the utility of exposure in the modification of pain-related avoidance. The present study compared the effects of exposure, non-exposure, and avoidance of pain on subsequent pain tolerance in 90 participants, using the iontophoretic administration of potassium ions as the pain stimulus. It was predicted that exposure would lead to an increase in pain tolerance when compared with non-exposure, and that avoidance would lead to a decrease in tolerance, when compared with both exposure and non-exposure. The effect of anxiety sensitivity, an individual difference variable thought to exacerbate fear of pain, was also examined. It was predicted that high levels of anxiety sensitivity would amplify the tolerance changing effects of exposure and avoidance. No significant differences were found in pain confrontation following the three experimental conditions. High levels of anxiety sensitivity were associated with a lower initial pain tolerance, and larger increases in tolerance following all the experimental conditions, when compared with low levels of anxiety sensitivity. This was interpreted in terms of a general exposure effect. A number of methodological issues were raised, and directions for future research were discussed.
Keywords: Avoidance (Psychology); Pain; Anxiety